EKOLITERASI SISWA MELALUI PENGELOLAAN SAMPAH DAN PELATIHAN PEMBUATAN ECOBRICK - Hidayati, Fajrina; Solida, Adila; Butar Butar, Marta; Rahmat, Andree Aulia (Jurnal Salam Sehat Masyarakat (JSSM), 2023)
Indonesia has main problems, namely basic education, the economy, and the environment based on the Global Competitive Index, which ranks 45 out of 140. The low level of eco-literacy is a serious problem that is of concern to the world for Indonesia. This is proven by Indonesia's crowning as the second country that contributes the most waste, especially plastic waste. Based on a national scope (assuming a population of 180 million people, the waste production rate for each person is two liters per day with a composition of 6.17%), the amount of waste accumulated in Indonesia annually reaches 1,599,000 tons. SDN 211/IV Jambi City already has rubbish bins that are differentiated based on the type of waste, namely organic and inorganic, however, the rubbish thrown into the rubbish bin is not grouped by type. Likewise, waste processing has not been managed properly, which has the potential to become a nest for disease-transmitting vectors due to the accumulation of waste behind schools. Ecoliteracy and one way of processing plastic waste is by eco-bricks. The solution offered is socialization and counseling about eco-literacy or increasing pro-environmental behavior as a basis that must be understood from an early age, especially the waste reduction paradigm, and providing technical guidance for making eco-bricks. The results were that students at SDN 211/IV Jambi City understood the importance of managing waste into eco-bricks and how to make them. Hopefully, this activity will continue in the future, and students can become cadres initiating plastic waste management in elementary schools in Jambi City.